(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
One of the key components of contemporary transportation systems is interchanges. As a result, this study provides a summary of the different kinds of simulation models that are frequently employed to assess the effectiveness metrics of the highways and interchanges as well as other implemented programs. It is possible to study and compare different traffic simulator software programs that applied these tactics in order to look into the various traffic simulation strategies to discuss several concepts and algorithms that can be used to simulate traffic systems in order to obtain more realistic results at the microscopic simulation level, this paper can provide a broad overview of the software packages under investigation, including their characteristics and differences like SYNCHRO 8, SIDRA INTERSECTION 5.1, (HCS) 2024, TRANSYT-7F, and multi-techninc in Spss profgramm like modular neural network (MNN), SVM, ANOVA, SARIMA, ARIMA. Choosing the model to employ in the simulation is one of the most difficult problems with traffic simulation tools. The best of these programs, according to the research findings, are those that can effectively and precisely depict the model and are more in line with reality, such as HCS 2024.